2020
DOI: 10.15809/irriga.2020v25n4p764-770
|View full text |Cite
|
Sign up to set email alerts
|

Conditioning of Seedlings of Peppers (Capsicum Annum L.), Influenced by the Hydroponic System "Floating"

Abstract: CONDITIONING OF SEEDLINGS OF PEPPERS (CAPSICUM ANNUM L.), INFLUENCED BY THE HYDROPONIC SYSTEM "FLOATING"     ANA RAQUEL PEREIRA DE MELO 1; JOSÉ FLÁVIO FERREIRA DE SOUSA2; CRISTIANE NUNES DA CONCEIÇÃO 3 E MARIA ROSELANE ALVES OLIVEIRA4   1 Engenheira Agrônoma, Instituto Federal do Maranhão - Campus Codó-MA, Rua do Poraquê S/N Codó Novo, Zona Rural, CEP: 65400000, Codó- MA, Brasil, anaraquel013@outlook.com; 2 Engenheiro Agrônomo, Instituto Federal do Maranhão - Campus Codó-MA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The efficiency of the floating system in optimizing the growth of several types of plants, including vegetables (Özer, 2018;Öztekin et al, 2018;Siaga et al, 2018;Giménez et al, 2019Giménez et al, , 2020Melo et al, 2020;Kanatas, 2020;Monteiro et al, 2020;Tsouvaltzis et al, 2020;Cristofano et al, 2021), cut flowers (Zanin et al, 2003;Barbaro et al, 2017), and aromatic and medicinal plants (Aktsoglou et al, 2021) has been previously demonstrated. However, data on bedding pot plants are scarce (Cros et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency of the floating system in optimizing the growth of several types of plants, including vegetables (Özer, 2018;Öztekin et al, 2018;Siaga et al, 2018;Giménez et al, 2019Giménez et al, , 2020Melo et al, 2020;Kanatas, 2020;Monteiro et al, 2020;Tsouvaltzis et al, 2020;Cristofano et al, 2021), cut flowers (Zanin et al, 2003;Barbaro et al, 2017), and aromatic and medicinal plants (Aktsoglou et al, 2021) has been previously demonstrated. However, data on bedding pot plants are scarce (Cros et al, 2007).…”
Section: Introductionmentioning
confidence: 99%